2020
DOI: 10.1111/agec.12552
|View full text |Cite
|
Sign up to set email alerts
|

The role of institutional quality on the performance in the export of coconut products

Abstract: The literature that addresses the role of institutions in bilateral trade is extensive. However, research that links institutional quality to specific products and their different levels of value addition is lacking. In this study, we look into institutional quality, based on three indicators from the World Bank's world governance indicators, and its indicator‐specific effects on bilateral coconut trade. In particular, we study coconut products with varying degrees of value addition. We use structural gravity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Other contributions consider specific geographical areas, as Martínez-Zarzoso and Márquez-Ramos (2019) do for selected Middle East and North African countries, where institutional quality improvements rise trade flows between 1996 and 2013. Other authors find a positive association between the quality of institutions and trade for agricultural products (Fiankor et al, 2019;Lin et al, 2020), which highlights the importance of sectoral specialization.…”
Section: Figure 4 World Governance Indicators For the Oecd And A Sampmentioning
confidence: 89%
See 1 more Smart Citation
“…Other contributions consider specific geographical areas, as Martínez-Zarzoso and Márquez-Ramos (2019) do for selected Middle East and North African countries, where institutional quality improvements rise trade flows between 1996 and 2013. Other authors find a positive association between the quality of institutions and trade for agricultural products (Fiankor et al, 2019;Lin et al, 2020), which highlights the importance of sectoral specialization.…”
Section: Figure 4 World Governance Indicators For the Oecd And A Sampmentioning
confidence: 89%
“…The impact of institutions on trade has attracted attention, especially since the works of Levchenko (2007) and Nunn (2007). Nevertheless, the main body of empirical studies covering the effect of institutions on trade has only considered the gross exports of goods (Méon & Sekkat, 2008;Francois & Manchin, 2013;Fiankor et al, 2019;Martínez-Zarzoso & Márquez-Ramos, 2019;Lin et al, 2020), services (Beverelli et al, 2017), or both (Álvarez et al, 2018). These studies do not distinguish between final goods and services or intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the institutional quality has been investigated from decades to come, the role of institutional context on value creation in agricultural sector has gained attention only in the last few years [16,50,13,51,14]. Through disparate analytical perspectives, several theoretical and empirical studies have shown different relations between institutional quality and economic performance in agricultural sector ( [6,14,51].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As for the agricultural sector, some authors have theoretically analyzed the effect of institutional context on economic performances of farms [14]. However, few researches have empirically investigated the effect of institutional quality on farm's economic performances [15,13,16]. Accordingly, the general goal of this study is to empirically investigate the effect of institutional quality on economic performances of Italian farms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, empirical macroeconomic studies have focused on the aggregate effects of efficient and better institutions. For instance, better and quality institutions are conducive for investment (Qu et al, 2017), promote growth and development (Acemoglu & Robinson, 2010; Aparicio et al, 2016; North, 1989; Sehrawat & Giri, 2019), improve productivity (Hall & Jones 1999; North, 1994; Zhu et al, 2019), increase access to financial services (Mertzanis & Said, 2019), encourage local and international trade (Asamoah et al, 2019), and promote export (Lin et al, 2020). These studies used country-level data to show that institutions matter for economic growth and development.…”
Section: Literature Reviewmentioning
confidence: 99%